Aktivitas Anti-inflamasi Ekstrak Etanol Daun Beluntas (Pluchea indica L.) pada Model Inflamasi Terinduksi CFA (Complete Freund's Adjuvant) : Anti-inflammatory Activity of Ethanol Extract of Beluntas Leaves(Pluchea indica L.) on Complete Freund's Adjuvant-induced Inflammatory Model - Reza Setiawan Sudirman; Usmar Usmar; Abdul Rahim; Muh. Akbar Bahar (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
A research about anti-inflammatory effect of Beluntas leaves extract on CFA (Complete Freund’s Adjuvant) induced inflammatory model has been conducted. The objective of this research was to determine the effect of Beluntas leaves extract in alleviating CFA-induced paw edema in mice (Mus musculus). The number of mice used was 15 and was divided into 5 groups. Group I was treated with NaCMC. Group II, III, and IV were given suspension of Beluntas leaves extract 100 mg/Kg, 300 mg/Kg, and 500 mg/Kg BW, respectively. Group V was a positive control treated with suspension of diclofenac sodium 0.1 ml/10 g orally. The determination of anti-inflammatory potency was based on the average time needed to ameliorate the edema volume. The shortest time period of edema reduction was produced by diclofenac sodium (within 9.33 days), then followed by Beluntas leaves extract with the concentration of 300 mg/Kg (within 12 days), 500 mg/Kg (within 14.33 days), and 100 mg/Kg (within 17.67 days), consecutively. These results are significantly different compared to negative control group which did not reduce the edema volume during 18 days of observation. In conclusion, ethanol extract of Beluntas leaves has an effective anti-inflamatory effect.